Lexical-semantic representation of body parts in Serbian child language - Anđelković, Darinka; Savić, Maja; Popović, Maša; Jakić Šimšić, Milena (Psihološka istraživanja, 2023)
In this study we explore how the conception and lexicon of human body in the native Serbian-speaking adult language is mirrored in the conception and lexicon of Serbian-speaking children. We explored how children of 5, 7, and 9 years used words and expressions to refer to the human body and its parts, and how these corresponded to the segmentation and lexicalization of the body in adult language. Participants were asked to name the body parts depicted in the drawings presenting the whole body (front, back) and face, with a red dot marking the specific body part. The results show that, with respect to most of face parts, arms, and legs, there is a gradual conceptual segmentation of the human body with age, reflected in a systematic decrease in the use of holons and a systematic increase in the use of merons in naming body parts. However, such hierarchical partonomic organization was not confirmed for other parts (eye, nose, ear, trunk, shoulders, neck, head), indicating a "shallow" organization at the mental level and revealing different strategies in the acquisition of lexicon. Children of all ages, especially 7- and 9-year-olds, seek alternative solutions for the body parts whose names are not in their vocabulary. Thus, they name adjacent body parts, internal organs, parts of the skeleton, or describe the surrounding areas. The results are discussed in light of previous findings from comparative developmental and cross-linguistic studies with respect to the universality and linguistic specificity of the recorded regularities of lexical development.
Keywords: body parts; lexical development; semantic development; meronymy; early school age; Serbian language